Формування поняття безпекового середовища як одного з елементів державних комунікацій - Денищук, Денис Євгенійович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The thesis of the scientific report proves that the concept of “security environment” is an important structural element of the information and communication sphere. It is emphasized that there is no normative consolidation of the term “security environment” in the current national legislation. The role of the “security environment” in the field of national security and the expediency of its formalization in the project “Strategy of Public Safety and Civil Defense of Ukraine” are characterized. The author’s definition of the term “security environment” is proposed.